Cultural Guilt pada Ibu Pekerja Jawa: Peran Self-Compassion dalam Menghadapi Ekspektasi Budaya tentang Ibu Ideal - Nanda Aristya; Marselius Sampe Tondok (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to understand the experiences of Javanese working mothers in dealing with Cultural Guilt and to examine the role of self-compassion in responding to cultural expectations of ideal motherhood. A qualitative phenomenological design was employed to explore the subjective meaning of their lived experiences through in-depth interviews with three Javanese working mothers. Data were analyzed using Interpretative Phenomenological Analysis (IPA), including repeated reading, initial coding, theme development, and cross-case interpretation. The findings indicate that Cultural Guilt arises from the tension between Javanese cultural norms—such as expectations of constant maternal presence and nurturing roles—and the realities of dual responsibilities at work and home. Guilt is intensified by cognitive resonance, where mothers attribute children’s difficulties or social comments to personal shortcomings. Emotional and physical impacts include exhaustion, anxiety, and reduced self-confidence. Nevertheless, self-compassion emerges as a key coping mechanism, expressed through self-kindness, common humanity, and mindfulness, supported by spousal affirmation and adaptive cultural values such as “nrimo ing pandum”. This study highlights that the experiences of working mothers are shaped not only by cultural pressures but also by strong psychological resilience that supports their well-being.